Community Participation in Combating COVID-19 Pandemic: Role of Local Clubs in Manipur - Devi, Aribam Pratima (SCHOOL SCIENCE, 2020)
The COVID-19 pandemic presents an unrivaled global crisis affecting countries and territories across the world. It has affected every aspect of our livelihood. India, with the second-largest population, is at a huge risk of the COVID-19 pandemic. It requires cooperation and collective preparedness from all strata in society. The transmission of COVID-19 could be reduced by a joint effort of the government and the community. In Manipur, local clubs play a vital role in the social well-being of the community. These voluntary and service-oriented bodies work towards the development of communities, empowerment of people, shaping youths, improving the quality of life, raising awareness in different realms, promotion of games and sports, preservation of culture and extending solidarity, etc. Considering the importance of local clubs, the present study investigates the role of local clubs in fighting the pandemic. The descriptive survey method was adopted to conduct the research. Data collection was done through telephonic and personal interviews. The findings revealed pivotal roles played by the local clubs ranging from the distribution of essential commodities to spreading awareness or helping the government isolate the individuals with travel history. The study suggests that working hand in hand with the community is the need of the hour. The government can control the spread of the COVID-19 transmissions with the nearby club's help.